Volume Reduction And Water Recovery Of Palm Oil Mill Effluent (POME) Using Membrane Distillation - Saat, Nor Azlinda Abdul (Universiti Sains Malaysia, 2017)
The palm oil mills are well-known for producing huge amounts of polluting effluent. Raw POME is acidic, has high temperature, suspended solid and most important, high organic biochemical oxygen demand (BOD). If it is not properly treated, it could pose environmental burden. To overcome this problem, membrane distillation is an alternative for the conventional treatment method as it could handle solution with high solid loading. In this study, a different concentration of POME (raw, sedimented and filtered) with different Total Suspended Solid (TSS) is filtered by using direct contact membrane distillation (DCMD) to recover the water at its original discharge temperature (80°C). The impact of POME deposition on the performance of MD membrane and their characterization such as contact angle, SEM, FTiR, porometry and LEP measurement were reported. It was found that POME deposition caused the decreased of the membrane contact angle due to the hydrophilic nature of POME suspended solid. The membrane has moderate flux (4.33 kg/m2h) and an excellence nutrient removal capability of more than 99%. Thus, pre-filtered POME is a practical way to be used in direct contact membrane distillation (DCMD) process in order to obtained high water recovery and mitigated the fouling tendency.